Tenth Review of IMF Data Standards Initiatives. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2022)
The IMF Data Standards Initiatives enhance data transparency as a global public good. The Tenth Review updates the framework, in light of new data priorities, through a parsimonious and principles-based expansion of encouraged data categories covering selected aspects in the areas of public debt, macro-financial indicators, foreign exchange intervention, climate change-related policy, and gender- disaggregated labor market statistics. The Review also focuses on strengthening the monitoring of the first tier of the Data Standards Initiatives, the enhanced General Data Dissemination System (e-GDDS), and encouraging subscribers of the second tier, the Special Data Dissemination Standard (SDDS), to modernize data publication technology.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Data Access; Methodology for Collecting, Estimating and Organizing Macroeconomic Data; Monetary Policy; Political Economy